ANALISIS KINERJA DAN VALUASI SEKTOR PERBANKAN INDONESIA: STUDI KASUS EMITEN BIG BANKS PERIODE MARET 2026 - Mundung, Deky Eko Wibowo (Jurusan Administrasi Bisnis Politeknik Negeri Manado, 2026)
This study analyses the fundamental performance and technical valuation of Indonesia's banking sector, focusing on four big banks in banking sector (BBCA, BBRI, BMRI, BBNI) during March 2026. Financial Services Authority data shows the banking industry remains solid with 9.49% year-on-year credit growth reaching Rp8,659 trillion, Non-Performing Loans declining to 2.14%, Capital Adequacy Ratio strong at 25.09%, and Return on Assets maintained at 2.47%. However, external pressures from Middle East geopolitical escalation drove significant stock price corrections of 7-11% throughout March 2026. Fundamental analysis reveals Q1 2026 net profit growth ranging from 3.80% to 17.05%, with BBRI recording the highest growth. Technical analysis indicates attractive valuations with BBRI's Price to Book Value at 1.4x (2.5 standard deviations below historical average) and BBNI at 1.1x. Relative Strength Index in oversold territory (32-38) signals potential trend reversal. The study concludes that the divergence between strong fundamentals and depressed prices creates attractive investment opportunities, recommending accumulation of BBCA, gradual buying of BBRI, holding BMRI, and speculative buying of BBNI for a 6–12-month horizon